Teachers perception of proactive and reactive children aggressiveness - Ushijima C., Rocío (2015)
This study is about the perception of teachers on proactive / reactive children aggresiveness of third and fourth grade of Primary School (8 to 11 years old). Its main purpose is to determine the reactive/ proactive perception of aggressiveness for teachers of third and fourth grade. For collecting the information was used the questionnaire of aggressiveness for teachers prepared by Sandra Cosi Muñoz, Andreu Vigil-Colet y Josepa Canals. The participants were 24, all of them tutors, of Ate, Lima. This study begins with arguments of children’s aggressiveness and its types. The methodology used is a transactional descriptive research with a comparative design. Research shows that for teachers participants do not exist significant differences between the scores of proactive and reactive aggression according to the age, speciality, marital status, years of service. However, by gender, it shows that there is a differential variable for reactive manifestation of aggressive behavior for women. The study concludes by recommending the importance of the difference between the two types of aggression to avoid bad consequences in the future.